Modulation by magnesium of N-methyl-D-aspartate receptors in developing human brain. Issue 2 (1st March 1998) - Chahal, H; D'Souza, S W; Barson, A J; Slater, P
Abstract : AIM: To investigate age related alterations in glutamate N -methyl-D-aspartate (NMDA) receptor binding produced by the modulatory compounds glutamate, glycine, and magnesium (Mg 2+ ) sulphate. METHODS: The effects produced by glutamate plus glycine, and Mg 2+ on the binding of [ 3 H]MK-801, a ligand for the N -methyl-D-aspartate ion channel phencyclidine site, were measured in membrane preparations made from prefrontal cortex from human neonate (n = 5), infant (n = 6), and adult (n = 6) necropsy brains. RESULTS: Neonatal brains had the least [ 3 H]MK-801 binding, suggesting either a low density of NMDA receptors or a more restricted access of [ 3 H]MK-801 to cation channel sites. Infant brains had the most [ 3 H]MK-801 binding which was stimulated to a greater extent by L-glutamate (100 μM) and glycine (10 μM) than in neonatal and adult brains. Mg 2+ invariably inhibited [ 3 H]MK-801 binding. However, the Mg 2+ IC50 value was higher in neonatal brain (3.6 mM) than infant (1.4 mM) and adult (0.87 mM) brains. CONCLUSION: Infant brain may have excess NMDA receptors which are hyper responsive to glutamate and glycine. The lower potency of Mg 2+ to inhibit [ 3 H]MK-801 binding in neonatal cortex may be because newborn babies have NMDA receptors without the normal complement of Mg 2+ sites. The findings suggest that therapeutic NMDA receptor block in neonates requires higher concentrations of magnesium sulphate in brain tissue.